2019
DOI: 10.1002/bsl.2429
|View full text |Cite
|
Sign up to set email alerts
|

The myth of school shooters and psychotropic medications

Abstract: There has been an assertion in certain parts of the media, especially social media, that the majority of individuals who have engaged in a school shooting were prescribed psychotropic medications prior to the event. To determine if there is any validity to this assertion, the authors of this article reviewed publicly available information regarding individuals involved in “educational shootings” per FBI publications for active shooters from 2000 to 2017. Sources of information included news reports with offici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Typically, most violent behavior by those who suffer from schizophrenia occurs before treatment is initiated (Buchanan et al, 2019). Other studies have also found that the initial and long-term treatment of schizophrenia with antipsychotic medication most likely decreases violence (Glick et al, 2019;Hall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, most violent behavior by those who suffer from schizophrenia occurs before treatment is initiated (Buchanan et al, 2019). Other studies have also found that the initial and long-term treatment of schizophrenia with antipsychotic medication most likely decreases violence (Glick et al, 2019;Hall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One infamous recent event occurred in 2012 at Sandy Hook Elementary School, where the gunman killed his mother before going to the school and killing 26 additional people, many of whom were children. 11,12 Because such events are rare, and because in these cases there is a high likelihood that the perpetrator is deceased (eg, died by suicide or killed by the police), much remains unknown about specific motivations and causative factors.…”
Section: Spree Killings That Start As Parricidementioning
confidence: 99%
“…Among those apprehended, many individuals raise some form of mental health defense, but the validity of their diagnosis may be undermined by concerns of possible malingering, especially in cases where the individual did not have a history of psychiatric treatment prior to the event. 11 In summary, based on FBI data, 12 spree shooters who committed parricide were usually male, in their late adolescence or early 20s, and more frequently targeted father figures. They often committed the parricide first and at a different location from later "active" shootings.…”
Section: Clinical Pointmentioning
confidence: 99%
“…To our knowledge, no study has ever found that most of those engaging in mass violence of any kind have a psychotic mental illness or are taking psychotropic medications, and this is what psychiatrists usually have in mind when they dismiss the assertion that mental illness or psychotropic medications are the primary cause of mass violence. For example, 2 publications based on a US Federal Bureau of Investigation (FBI) study of active shooters from 2000 to 2013 found that only 25% of perpetrators had ever received a diagnosis of mental illness and concluded, “[A]bsent specific evidence, careful consideration should be given to social and contextual factors that might interact with any mental health issue before concluding that an active shooting was ‘caused’ by mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…In short, declarations that all active shooters must simply be mentally ill are misleading and unhelpful." Likewise, Hall et al 1 reviewed available information regarding individuals involved in educational institution shootings per the FBI publications on active shooters from 2000 to 2017 and found that most school shooters were not previously treated with psychotropic medications and concluded that "by either the primary measure of documented psychotropic treatment at any time prior to the event, or the secondary measure of a successful NGRI (not guilty by reason of insanity) defense, it does not appear that most school shooters had been prescribed psychotropic medications prior to the shooting or were negatively impacted by the medications." IMPORTANCE Psychiatry has struggled to clarify the types of mental turmoil that are associated with mass violence.…”
mentioning
confidence: 95%